Multi-mode hybrid reconfigurable PUF circuit design based on linear feedback - Luan Zhicun; Zhang Yuejun; Wang Jiawei; Pan Zhao (Dianzi Jishu Yingyong, 2018)
The physical unclonable function(PUF) circuit is a special recognition technology in the chip field. By extracting random deviations of the manufacturing processes it generate unlimites number of special keys. In this paper, a multi-mode hybrid reconfigurable PUF(Mhr-PUF) scheme based on linear feedback is proposed. The proposed PUF includes the storage PUF circuit, linear feedback shift register and arbiter PUF circuit. Firstly, random source of storage is used to generate the selection signal of the self-selection feedback network, which achieves the random selection function of the feedback network. Then, linear feedback shift register generates random number sequence according to the feedback signal. It is used as the n bits path selection signal of the arbiter PUF to implement the serial key of Mhr-PUF. Finally, the proposed Mhr-PUF circuit is designed under TSMC 65 nm process. Experiment results show that the randomness is 96.2% and the uniqueness is 50.8%.